Duck Plague Virus pUL48 Protein Activates the Immediate-Early Gene to Initiate the Transcription of the Virus Gene - Zhou, Tong; Fan, Dengjian; Wang, Mingshu; Cheng, Anchun; Wu, Ying; Yang, Qiao; Tian, Bin; Jia, Renyong; Ou, Xumin; Mao, Sai; Sun, Di; Zhang, Shaqiu; et al. (Frontiers in Microbiology, 2021)
Duck plague caused by the Duck plague virus (DPV) is an infectious disease that seriously harms the waterfowl breeding industry. The VP16 protein of α herpes virus can bind to specific cis-acting elements upstream of the immediate-early (IE) gene's promoter to promote the IE gene's transcription, so it is also called the trans-inducer of IE gene (α-TIF). However, no studies on DPV α-TIF have been reported. This study investigated the UL48 gene encoding protein (pUL48) transcriptional activation region, target sequence, and viral protein affecting its transcriptional activation using a dual-luciferase reporter gene detection system, and pUL48 was identified as the α-TIF of DPV. (1) The regulation of pUL48 on DPV different gene promoters showed that pUL48 could activate all the promoters of immediate early genes (ICP4, ICP22, and ICP27) but not the promoters of early and late genes. (2) The activity of pUL48 to ICP4 and ICP22 promoters with different upstream lengths showed that pUL48 activated ICP4 and ICP22 promoters by acting on TAATGA (T) TAT element upstream of ICP4 promoter and TAATTATAT element upstream of ICP22 promoter, respectively. (3) Transcriptional activation of IE gene by truncated proteins of different lengths at the N-terminal of pUL48 was detected. The results showed that the transcriptional activation domain of pUL48 was amino acid 1-60 at the N-terminal, and amino acid 1-20 was its core region. In addition, it was found that pUL14, pUL46, and pUL47 significantly promoted the transcriptional activation of pUL48. The effects of loss of pUL47 and its nuclear localization signal on the nuclear entry and transcriptional activation function of pUL48 were further examined. The results showed that pUL47 could promote the nuclear entry of pUL48 throμgh its nuclear localization signal at positions 40-50 and 768-777 amino acids, thus enhancing the transcriptional activation function of pUL48 and synergistic promotion of viral gene transcription.